Building the Integrity of Urban Development Planner Through Corruption Risk Management and Assessment: Literature Review - Lilin Budiati (The Journal of Indonesia Sustainable Development Planning, 2020)
Planning in the broadest sense covers definition and selection of needs to evaluation and audit phase. Planning and planners have unique and strategic positions, roles, and functions, because they bring together two sides of interests: public sector interests and private sector interests. This uniqueness causes the field of planning and planners to have a political role and bargaining position in the development planning process. This political role can cause the presence of two sides, which are the bright side as the planner with integrity, who can design internal control systems and risk management for prevention and detection of corruption, and the dark side as the conspirator with public officials and the contractor or business corporation to bring corruption together. The dark side of planning becomes the entry point for corruption and/or fraud. The bright side of planning can be used to build the integrity of community and society, through the application of internal control systems and risk management that are based on specific corruption indicators such as Government Institution Risk Indicator (GIRI), Contractor Risk Indicator (CRI), and Political Connection Indicator (PCI).